1998
DOI: 10.1159/000027995
|View full text |Cite
|
Sign up to set email alerts
|

Massive Proteinuria as a Main Manifestation of Primary Antiphospholipid Syndrome

Abstract: Renal involvement in antiphospholipid syndrome (APS) is increasingly reported. So far, massive proteinuria as the principal feature of primary APS (PAPS) has not been well documented. We describe 3 patients with PAPS and massiv proteinuria. Renal biopsy was performed in all 3, and features consistent with membranous and focal segmental glomerulopathy were disclosed. These histological lesions were not yet reported in PAPS. We conclude that the spectrum of renal lesions in PAPS is diverse and that it should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
2
10
0
Order By: Relevance
“…There are case reports demonstrating that adding warfarin, heparin, or aspirin to the standard treatment offers advantages in aPL-nephropathy patients by improving their renal function (144)(145)(146) and enhancing blood flow in interlobar, segmental, and arcuate arteries (147). However, there are no controlled studies and, despite adequate anticoagulation, renal lesions develop in some APS patients (148, 149) and recur after kidney transplantation, often leading to graft loss (150).…”
Section: Renal Impairmentmentioning
confidence: 99%
“…There are case reports demonstrating that adding warfarin, heparin, or aspirin to the standard treatment offers advantages in aPL-nephropathy patients by improving their renal function (144)(145)(146) and enhancing blood flow in interlobar, segmental, and arcuate arteries (147). However, there are no controlled studies and, despite adequate anticoagulation, renal lesions develop in some APS patients (148, 149) and recur after kidney transplantation, often leading to graft loss (150).…”
Section: Renal Impairmentmentioning
confidence: 99%
“…Case reports of antiphospholipid syndrome presenting with proteinuria showed that the renal involvement in this syndrome could also be in different forms of glomerulonephritis (membranous, focal proliferative) without any sign of glomerular thrombosis [8, 9]. No report on the presence of antiphospholipid antibodies in meningococcal disease was encountered in a literature review and, therefore, the pathophysiology of this concurrence in the present case needs elucidation.…”
Section: Discussionmentioning
confidence: 85%
“…Advanced CKD was detected in 9 of the 20 aPL antibodiypositive patients (45%) and 6 patients of the 20 patients were classified with class IV, suggesting that class IV may be associated with the progression of CKD. In previous studies, a number of patients with aPL antibody positivity and nephrotic syndrome showed membranous nephropathy at renal biopsy (28,29). This discrepancy is thought to be possibly explained by the differences in the characteristics of the study population.…”
Section: Discussionmentioning
confidence: 92%